Pengaplikasian Literasi Wirausaha Digital Yang Mendorong Tumbuhnya Motivasi Pengembangan Usaha Santanamekar Kabupaten Tasikmalaya - Adi Prehanto; Btari Mariska Purwaamijaya; Oding Herdiana; Muhammad Dzikri Ar Ridlo; Adam Hermawan; Alifia Fatimatun Nazya (Jurnal Pengabdian Nasional (JPN) Indonesia, 2024)
The industrial revolution 4.0 has brought many developments, the era of automation has been implemented in several sectors to make activities more effective and artificial intelligence is the driving force in this era, which promises many conveniences in various fields. Based on the results of research entitled "Perceptions and Prospective Analysis of Artificial Intelligence and its impact on Human Resources in the Indonesian Industry 4.0," Human Resources in Industry is a crucial variable in changes in Indonesia's movement to prepare for industry 4.0. Industry 4.0 can be interpreted as an industrial era in which all entities or devices within it are made able to communicate with each other in real time at any time by utilizing internet technology, in order to achieve the goal of creating new value or optimizing existing value from every process in the industry. . The results of the pre-test and post-test on 8 respondents showed an increase after the pre-test of 87.5%, which was dominated by housewives in the digital entrepreneurship strategy workshop. Based on the results of 2 studies, it was found that there is a need for training that can apply digital technology to help them professionally by adapting to the demands of industry 4.0 and the role of university teaching staff to engage with the community in empowerment who have experience not only as academics, but also as practitioners who have pedagogical, professional and social competency abilities so that they attract more interest.